تأثير بعض العوامل البيئية على توزع العوالق النباتية في شاطئ مدينة طرطوس - حمود نديم; ديب جورج; سلوم أمامه (Latakia University Journal -Biological Sciences Series, 2016)
أجري هذا البحث البيئي على المياه الشاطئية لمدينة طرطوس لأول مرة ، استكمالاً للدراسات السابقة على امتداد الشاطئ السوري ، ولقد تم اختيار محطات الدراسة اعتماداً على خصائصها البيئية المختلفة فيما بينها ، وتعرضها المستمر لمصادر تلوث متنوعة (نفطية، كيميائية، عضوية،..) ، ولقد تم تنفيذ 13 طلعة بحرية خلال فترة الدراسة ، التي امتدت من أيلول 2013م ولغاية أيلول 2014م ، إذ جمعت خلالها عينات مائية لتحليلها ، وتحديد تركيز بعض الشوارد المغذية فيها، كما جمعت عينات حيوية لدراستها ، وتحديد أنواع العوالق النباتية فيها، إضافةً إلى إجراء قياسات حقلية لبعض الخصائص الفيزيائية والكيميائية لمياه البحر (درجة الحرارة، الرقم الهيدروجيني، درجة الملوحة تركيز الأوكسجين المنحل) ، سجل في هذه الدراسة 160 نوعاً من العوالق النباتية في جميع مواقع الدراسة ، توزعت كالتالي:91 نوعاً من الطحالب الذهبية ، 50 نوعاً من الطحالب النارية، 11 نوعاً من الطحالب الخضراء ، و8 أنواع من الطحالب الزرقاء ، اختلف توزعها من موقع لآخر ، ومن شهر لآخر باختلاف الظروف البيئية . This environmental research was conducted on the coastal water of Tartous city for the first time to complement previous studies along the Syrian coast. Sampling station were selected based on their different environmental characteristics from each others on one hand, and their continuous exposure to the sources of pollution (oil, chemical, organic) on the other hand. It hasbeen implemented13sortiesfreelyduring the study period, which lasted fromSeptember2013untilSeptember2014. during which water samples were collected for analysis and determine the concentration of nutrients in, as vital samples to study and determine the types of phytoplankton, which collected, in addition to conducting field measurements of some properties Physical seawater (temperature, pH, salinity, oxygen dissolved concentration). This study has recorded 160 species of phytoplankton in study sites, distributed as follows: 91 species of Chryssophyta, 50 of Pyrrophyta, 11 of Chlorophyta, and 8 of Cyanophyta, their distribution has differed from one site to another and from month to monthaccordingto the differentiation in the environmental conditions.